Performance of different rubber tree clones against South American leaf blight (Microcyclus ulei) - Silva, L. G.; Junior, W. C. J.; Souza, A. F.; Alves, F. R.; Furtado, Edson Luiz [UNESP] (Wiley-Blackwell, 2014)
This study was aimed to evaluate the behaviour of eighteen clones of Hevea brasiliensis (rubber) against South American leaf blight and to study progress of the disease. The experiment was conducted in Cachoeiro de Itapemirim-ES, where 18 clones were evaluated. The experimental design was a randomized block with four replicates; each experimental unit consisted of three plants. Evaluations were performed at 15-day intervals on 30 leaflets per tree. Disease incidence was quantified and infection classified according to the stages of development and type of damage. Leaf blight occurred during the entire experimental period; however, disease intensity varied with the resistance level of the clones and the time of year. Clones FX 3864, RRIM 725, RRIM 711, IAC 300 and IAN 873 exhibited the highest resistance to leaf blight.